y+LAT1 and y+LAT2 contribution to arginine uptake in different human cell models: Implications in the pathophysiology of Lysinuric Protein Intolerance - Rotoli, Bianca Maria (J Cell Mol Med, 2019)
y+LAT1 (encoded by SLC7A7), together with y+LAT2 (encoded by SLC7A6), is the alternative light subunits composing the heterodimeric transport system y+L for cationic and neutral amino acids. SLC7A7 mutations cause lysinuric protein intolerance (LPI), an inherited multisystem disease characterized by low plasma levels of arginine and lysine, protein‐rich food intolerance, failure to thrive, hepatosplenomegaly, osteoporosis, lung involvement, kidney failure, haematologic and immunological disorders. The reason for the heterogeneity of LPI symptoms is thus far only poorly understood. Here, we aimed to quantitatively compare the expression of SLC7A7 and SLC7A6 among different human cell types and evaluate y+LAT1 and y+LAT2 contribution to arginine transport. We demonstrate that system y+L‐mediated arginine transport is mainly accounted for by y+LAT1 in monocyte‐derived macrophages (MDM) and y+LAT2 in fibroblasts. The kinetic analysis of arginine transport indicates that y+LAT1 and y+LAT2 share a comparable affinity for the substrate. Differences have been highlighted in the expression of SLC7A6 and SLC7A7 mRNA among different cell models: while SLC7A6 is almost equally expressed, SLC7A7 is particularly abundant in MDM, intestinal Caco‐2 cells and human renal proximal tubular epithelial cells (HRPTEpC). The characterization of arginine uptake demonstrates that system y+L is operative in renal cells and in Caco‐2 where, at the basolateral side, it mediates arginine efflux in exchange with leucine plus sodium. These findings explain the defective absorption/reabsorption of arginine in LPI. Moreover, y+LAT1 is the prevailing transporter in MDM sustaining a pivotal role in the pathogenesis of immunological complications associated with the disease.